GREEN AND INNOVATIVE TRANSFORMATIONS FOR GLOBALIZING CITIES - Лариса Саркісян; Марія Варламова (Економіка та суспільство)
Cities are engines of economic growth and competitiveness and simultaneously key sources of ecological and social vulnerability. Urban areas create networks interlinked with common economic, cultural, social, environmental, and digital processes which help attract international flows of capital and talent. As a result, the global climate change agenda, energy issues, intense migration, and changing security challenges lead to reshaping urban development policies in an increasingly globalizing world, prioritizing the combination of approaches that enhance growth and sustainability principles. In this paper, we discuss how rethinking established approaches to urban development, effective strategic and tactical spatial planning, a high degree of economic and social integration into global processes, green energy transformation, and security provision can increase city competitiveness. We then identify the main factors and consequences of urban transformation in the context of involvement in global economic processes in chosen regions. Against this background, we suggest priority actions of strategic planning process aiming to intensify Ukrainian cities’ integration into the global economy (case studies of Kyiv and Lviv) during the war and post-war recovery and reconstruction. It is expected that the study’s results will clarify the vision of cities as engines of global and local economic growth and define the key priorities of strategic planning in the transformation period. On that basis, adaptation to new economic, social, and ecological conditions and processes will significantly increase the efficiency of urban management practices, namely, to the city’s emergence as an innovation hub. A self-sustaining innovation ecosystem that is capable of implementing the technologies of the Fourth Industrial Revolution and positively reshaping the quality of life in urban areas. In such circumstances, the ability to respond to shocks of different levels will be a key sign of the resilience of globalizing cities. The findings can be limited by a small sample of cities for research and the lack of available and/or reliable data due to incomplete scattered and hidden due to security issues information about urban development.